A family-centered evaluation of psychosocial agendas in spina bifida - (:unkn) unknown (Springer Milan, 2008)
Care patterns and parenting quality have an important effect on the infant-caregiver relationship, as well as on the developmental outcomes of children [1]. High quality care is linked to higher cognitive ability and higher social competence in children [2]. Especially in the case of disability, families and other close networks gain a pivotal role as the main caregivers for the child [3]. Currently, the role and needs of families attract considerable attention due to the growing amount of evidence regarding their participation in the illness process and the attached psychosocial outcomes. © 2008 Springer-Verlag Italia.